Holistic Education in Character Building for Children in the Digital Era: A Maqasid al-Shariah Perspective - Siti Marhamah; Andri Gunawan; Siti Nur Riani (SALAM: Jurnal Sosial dan Budaya Syar-i, 2026)
The digital era has brought both opportunities and challenges to children's character development. Easy access to information, social media, and digital technologies offers significant benefits for learning processes; however, it also has the potential to contribute to moral degradation, identity crises, and weakened self-control among children. This article aims to analyze the concept of holistic education in shaping children's character in the digital age from the perspective of Maqasid al-Shariah. The study employs a library research method with a descriptive qualitative approach. The data were obtained from literature on holistic education, character education, child development, the digital era, and the theory of Maqasid al-Shariah. The findings indicate that holistic education grounded in Maqasid al-Shariah serves as an integrative paradigm for character formation through the protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-'aql), lineage (hifz al-nasl), and wealth (hifz al-mal). These five dimensions are highly relevant in addressing digital challenges such as the spread of harmful content, cyberbullying, gadget addiction, misinformation, and consumerist behavior. Holistic education based on Maqasid al-Shariah emphasizes a balance among intellectual, emotional, social, spiritual, and digital intelligences, thereby fostering a generation that is morally grounded, ethical, responsible, and capable of using technology wisely.